Técnicas de belleza de manicure y pedicure y su incidencia en el proceso de enseñanza aprendizaje a estudiantes de la Unidad de Formación Artesanal 5 de Noviembre del cantón Naranjal provincia del Guayas - Aquino Medina, Josefina Victoria (2018)
The present theme of beauty research has progressed constantly in the world where the need to be well every day becomes more important in this society where self-esteem values and health and the physical and all aspects of aesthetics becomes characteristics that fortunate or unfortunate place people in a social, professional and work place for this reason personal care is really very important for the intellectual development of each person. The need to move forward the economy and development of the country entrepreneurs have adopted new lines of innovation in beauty and cosmetology to compete in the labor market where education plays an important role for the capacity of thought and ideas of people their participation in valuable in the technological changes that contribute to the change of the country where the development and the process of new techniques and methods of beauty, cosmetology and facials. In this way it is proposed to determine the incidence of beauty techniques of Manicure and Pedicure in the Teaching Process, Learning to students of the Artisanal Training Unit November 5, and Canton Naranjal of the Province of Guayas